Transcoding-Based Error-Resilient Video Adaptation for 3G Wireless Networks. (8th July 2007) - Eminsoy Eminsoy, Sertac Sertac; Dogan Dogan, Safak Safak; Kondoz Kondoz, Ahmet M. Ahmet M.
Abstract : Transcoding is an effective method to provide video adaptation for heterogeneous internetwork video access and communication environments, which require the tailoring (i.e., repurposing) of coded video properties to channel conditions, terminal capabilities, and user preferences. This paper presents a video transcoding system that is capable of applying a suite of error resilience tools on the input compressed video streams while controlling the output rates to provide robust communications over error-prone and bandwidth-limited 3G wireless networks. The transcoder is also designed to employ a new adaptive intra-refresh algorithm, which is responsive to the detected scene activity inherently embedded into the video content and the reported time-varying channel error conditions of the wireless network. Comprehensive computer simulations demonstrate significant improvements in the received video quality performances using the new transcoding architecture without an extra computational cost.